A review on nearly isothermal compression technology. (December 2022) - Kim, Timothy; Lee, Cheng-Yi; Hwang, Yunho; Radermacher, Reinhard
Highlights: Water injection is highly effective in increasing heat transfer. "Chamber packing" provides a passive, inexpensive method of increasing heat transfer. The plethora of studies on simulations and cycles analytics. Need for experimental validation and long-term performance analysis. Need for new ways in achieving isothermal compression in refrigeration applications. Abstract: Compressors can be described as the heart of a vapor compression refrigeration system, circulating the working fluid in the system. Significant benefits can be gained from improving its efficiency since energy consumption is responsible for almost the entire system's power input. An effort has been made to achieve isothermal compression through liquid refrigerant injection or inter-stage cooling in refrigeration systems. In recent years, much effort has been invested into isothermal compression technology for air compressors or compressed air energy storage systems with the rise of renewable energy. This work has explored the advancements made in this area and categorized them to discuss the benefits, limitations, and tradeoffs. Evidently, increasing heat transfer area is a significant aid in improving heat transfer, resulting in better isothermal compression. However, liquid pistons open more avenues for this to be pursued, and therefore, are limited to air compression applications. In addition, water injection proved to be the most effective among the methods. Finally, there is a need for more experimental research on refrigeration applications and the field is still in its infancy.